The assessment of serum-mediated phagocytosis of necrotic material by polymorphonuclear leukocytes to diagnose and predict the clinical features of systemic lupus erythematosus: an observational longitudinal study. Issue 1 (December 2016) - Compagno, Michele; Gullstrand, Birgitta; Jacobsen, Søren; Eilertsen, Gro; Nilsson, Jan; Lood, Christian; Jönsen, Andreas; Truedsson, Lennart; Sturfelt, Gunnar; Bengtsson, Anders
Abstract Background Serum-mediated phagocytosis of antibody- and complement-opsonized necrotic cell material (NCM) by polymorphonuclear leukocytes can be quantified by using a flow cytometry–based assay. The phagocytosis of necrotic cell material (PNC) assay parallels the well-known lupus erythematosus cell test. In this study, we aimed to investigate the diagnostic accuracy of the assay and the relationship with clinical manifestations and disease activity in systemic lupus erythematosus (SLE). Methods The diagnostic accuracy for SLE diagnosis of the PNC assay was studied by cross-sectional assessment of blood samples from 148 healthy control subjects and a multicenter rheumatic group (MRG) of 529 patients with different rheumatic symptoms. A cohort of 69 patients with an established SLE diagnosis (SLE cohort) underwent longitudinal clinical and laboratory follow-up for analysis of the temporal relationships between PNC positivity and specific clinical manifestations. Results In 35 of 529 MRG patients, 13 of whom had SLE, the PNC assay result was positive. Combined positivity of the PNC assay and anti–double-stranded DNA antibodies increased specificity and positive predictive value for SLE diagnosis to 0.99 and 0.67, respectively. In the longitudinal study, 42 of 69 SLE cohort patients had positive results in the PNC assay at least once. PNC assay positivity was associated with current hematological manifestations and could predict mucocutaneous manifestations. When combined with hypocomplementemia, PNC positivity preceded increased Systemic Lupus Erythematosus Disease Activity Index 2000 score, glomerulonephritis, and alopecia. Conclusions Serum-mediated PNC by polymorphonuclear leukocytes is commonly but not exclusively seen in patients with SLE. The PNC assay may be used in follow-up of patients with SLE and, especially in combination with other routinely assessed laboratory tests, may help to predict flares and different clinical manifestations, including glomerulonephritis. Our results encourage further development of the PNC assay as a complementary laboratory tool in management of patients with SLE.